Nuclear ADP-ribosylation drives IFNγ-dependent STAT1α enhancer formation in macrophages - Rebecca Gupte (Nature Portfolio, 2021)
STAT1a is required for pro-inflammatory responses in macrophages. Here the authors reveal that post-translational modification of STAT1a, ADPribosylation, plays a critical role in enhancer formation and activation, thus modulating IFNγ-stimulated inflammatory responses in macrophages.